DESIGN OF VISITOR MANAGEMENT SYSTEM APPLICATION IN THE INTERLINK LOBBY OF SEJAHTERA DATA CENTER - Andi Prastomo; Yossi Indrawati Syuhardi (Journal of Information System, Informatics and Computing, 2023)
A Visitor Management System (VMS) is a sophisticated application created to monitor the comings and goings of visitors at a particular location. Interlink Data Center Sejahtera's lobby is an important space that welcomes many visitors including employees, business associates and outside guests. To maintain a high level of security and efficiency in visitor management, an all-encompassing system is essential to meet the unique demands of the lobby. The purpose of this design is to create a VMS application that can automate the registration process, security checks, and recording of visitor visits at the Interlink Data Center Sejahtera Lobby. The Research and Development method can be used to develop the Visitor Management System (VMS) application in the Interlink Data Center Sejahtera lobby. By designing this VMS application, it is hoped that visitor management at the Interlink Data Center Sejahtera lobby can be more efficient, safe and well documented. This application can increase security, provide a good visitor experience, and facilitate overall visit management.